Formation of nanocrystalline GeSn thin film on Si substrate by sputtering and rapid thermal annealing. (October 2016) - Mahmodi, H.; Hashim, M.R.; Hashim, U.
Abstract: Nanocrystalline Ge1-x Snx thin films have been formed after rapid thermal annealing of sputtered GeSn layers. The alloy films were deposited onto the Silicon (100) substrate via low cost radio frequency magnetron sputtering. Then, the films were annealed by rapid thermal annealing at 350 °C, 400 °C, and 450 °C for 10 s. The morphological, structural, and optical properties of the layers were investigated with field emission scanning electron microscopy (FESEM), Energy-dispersive X-ray spectroscopy (EDX), Raman spectroscopy, and high-resolution X-ray diffraction (HR-XRD). The Raman analysis showed that the only observed phonon mode is attributed to Ge-Ge vibrations. Raman phonon intensities of GeSn thin films were enhanced with increasing the annealing temperature. The results clearly revealed that by increasing the annealing temperature the crystalline quality of the films were improved. The XRD measurements revealed the nanocrystalline phase formation in the annealed films with (111) preferred orientation. The results showed the potentiality of using the sputtering technique and rapid thermal anneal to produce crystalline GeSn layer. Highlights: Nanocrystalline GeSn thin film were formed by sputtering and rapid thermal annealing. The influences of annealing temperature on the evolution of characteristics are discussed. The XRD results confirm the nanocrystalline phase formation of the annealed films. Upon heat treatment, the crystalline quality of the thin films were increased.